Analisis Hukum atas Peralihan Hak yang Didasarkan Penyalahgunaan Keadaan yang Dilakukan oleh Pembeli: Studi Putusan Nomor 47 PK/Pdt/2025 - Karryn Young; hasim purba; suprayitno (Jurnal Hukum Lex Generalis, 2026)
Transfer of rights through a Sale and Purchase Deed (AJB) does not always occur under balanced conditions between the parties, particularly when preceded by a debt relationship that may give rise to abuse of circumstances (misbruik van omstandigheden), as reflected in Decision No. 47/PK/Pdt/2025. This study employs a normative juridical method with statutory and case approaches, analyzed qualitatively. The findings indicate that the debtor’s economic distress was exploited by the creditor to transfer land rights to another party, resulting in an unequal bargaining position and defective consent. Such abuse affects the validity of the AJB and the land certificate, which were ultimately declared null and void by the court. The decision underscores the importance of applying the principle of good faith and providing legal protection to the weaker party in every process of land rights transfer.